Stressful crystal histories recorded around melt inclusions in volcanic quartz - Tyler Cadena; Michael Manga; Kenneth Befus; Nobumichi Tamura (Contributions to Mineralogy and Petrology, 2024)
Magma ascent and eruption are driven by a set of internally and externally generated stresses that act upon the magma. We present microstructural maps around melt inclusions in quartz crystals from six large rhyolitic eruptions using synchrotron Laue X-ray microdiffraction to quantify elastic residual strain and stress. We measure plastic strain using average diffraction peak width and lattice misorientation, highlighting dislocations and subgrain boundaries. Quartz crystals across studied magma systems preserve similar and relatively small magnitudes of elastic residual stress (mean 53–135 MPa, median 46–116 MPa) in comparison to the strength of quartz (~ 10 GPa). However, the distribution of strain in the lattice around inclusions varies between samples. We hypothesize that dislocation and twin systems may be established during compaction of crystal-rich magma, which affects the magnitude and distribution of preserved elastic strains. Given the lack of stress-free haloes around faceted inclusions, we conclude that most residual strain and stress was imparted after inclusion faceting. Fragmentation may be one of the final strain events that superimposes stresses of ~ 100 MPa across all studied crystals. Overall, volcanic quartz crystals preserve complex, overprinted deformation textures indicating that quartz crystals have prolonged deformation histories throughout storage, fragmentation, and eruption.

Elastic thermobarometry on metapelites across the crustal section of the Famatinian Arc, Argentina - Emanuel Giovanini; Kenneth S. Befus; Juan E. Otamendi; Eber Cristofolini; Tomas Guerreiro; Miguel Cisneros (Contributions to Mineralogy and Petrology, 2024)
We applied elastic thermobarometry on garnet-bearing migmatites along two transects through the crustal section at Sierra Valle Fértil-La Huerta, Argentina. We performed quartz-in-garnet barometry and zircon-in-garnet thermometry on metapelites from different paleo-depths across the crustal section. Our work recovers entrapment pressures ranging from 240 to 1330 MPa and entrapment temperatures between 691 and 1574 °C. The entrapment conditions are broadly consistent with anticipated pressures and temperatures along the crustal section derived previously using conventional, thermodynamic thermobarometers. The quartz-in-garnet barometer reproduces those conventionally established entrapment conditions when samples only experienced conditions within the alpha-quartz stability field. Raman-derived pressures for samples that experienced beta-quartz reference conditions are commonly much higher than those established by conventional barometry. Samples that preserve compressive (positive) residual pressures best reproduce reference entrapment pressures. Entrapment temperatures show high variability and overestimation of temperature conditions compared to conventional results. These results indicate elastic thermobarometry over- or under-estimates crystallization conditions in rocks crystallized at high temperatures, as is common in the Famatinian Arc deep-crust. We suggest that modeling quartz behavior across the alpha–beta transition may present challenges, as does shape maturation, viscous deformation, and radiation damage in zircon.

Quartz-hosted inclusions and embayments reveal storage, fluxing, and ascent of the Mesa Falls Tuff, Yellowstone - Kenneth S. Befus; Anna C. Ruefer; Chelsea M. Allison; James O. Thompson (Earth and Planetary Science Letters, 2023)

Supersaturation Nucleation and Growth of Plagioclase: a numerical model of decompression-induced crystallization - Benjamin J. Andrews; Kenneth S. Befus (Contributions to Mineralogy and Petrology, 2020)

Crystal nucleation and growth produced by continuous decompression of Pinatubo magma - Kenneth S. Befus; Benjamin J. Andrews (Contributions to Mineralogy and Petrology, 2018)

Magma storage and evolution of the most recent effusive and explosive eruptions from Yellowstone Caldera - Kenneth S. Befus; James E. Gardner (Contributions to Mineralogy and Petrology, 2016)

Ascent and emplacement dynamics of obsidian lavas inferred from microlite textures - Kenneth S. Befus; Michael Manga; James E. Gardner; Matthew Williams (Bulletin of Volcanology, 2015)

Experimental constraints on rhyolite-MELTS and the Late Bishop Tuff magma body - James E. Gardner; Kenneth S. Befus; Guilherme A. R. Gualda; Mark S. Ghiorso (Contributions to Mineralogy and Petrology, 2014)

Pre-eruptive storage conditions and eruption dynamics of a small rhyolite dome: Douglas Knob, Yellowstone volcanic field, USA - Kenneth S. Befus; Robert W. Zinke; Jacob S. Jordan; Michael Manga; James E. Gardner (Bulletin of Volcanology, 2014)

Stable chlorine isotope behavior during volcanic degassing of H2O and CO2 at Mono Craters, CA - Jaime D. Barnes; Timothy J. Prather; Miguel Cisneros; Kenneth Befus; James E. Gardner; Toti E. Larson (Bulletin of Volcanology, 2014)

Compositional gradients surrounding spherulites in obsidian and their relationship to spherulite growth and lava cooling - James E. Gardner; Kenneth S. Befus; James Watkins; Marc Hesse; Nathan Miller (Bulletin of Volcanology, 2012)